Rapid research response to the COVID-19 pandemic: perspectives from a National Institute for Health Biomedical Research Centre - Lorna R. Henderson; Helen McShane; Vasiliki Kiparoglou (BMC, 2022)
Abstract With over 5 million COVID-19 deaths at the time of writing, the response of research leaders was and is critical to developing treatments to control the global pandemic. As clinical research leaders urgently repurposed existing research programmes and resources towards the COVID-19 pandemic, there is an opportunity to reflect on practices observed in Biomedical Research Centre (BRC) settings. BRCs are partnerships between leading National Health Service organizations and universities in England conducting translational research for patient benefit funded by the National Institute for Health Research (NIHR). Oxford BRC-supported researchers have led the rapid set-up of numerous COVID-19 research studies at record speed with global impact. However, the specific contribution of BRCs to the COVID-19 pandemic in the literature is sparse. Firstly, we reflect on the strategic work of clinical research leaders, creating resilient NIHR research infrastructure to facilitate rapid COVID-19 research. Secondly, we discuss how COVID-19 rapid research exemplars supported by Oxford BRC illustrate "capacity", "readiness" and "capability" at an organizational and individual level to respond to the global pandemic. Rapid response research in turbulent environments requires strategic organizational leadership to create resilient infrastructure and resources. The rapid research exemplars from the Oxford BRC illustrate capability and capacity at an organizational and individual level in a dynamic environment to respond during the COVID-19 public health challenge. This response was underpinned by swift adaptation and repurposing of existing research resources and expertise by the Oxford BRC to deliver rapid research to address different aspects of COVID-19.